Sedition Laws and the Requirement of Incitement to Imminent Disorderly Conduct: A Critical Analysis of Chihana v. Republic. - Mhango, Owen (Institute of Criminology, 2014)
This article reviews the application of laws against sedition in Southern Africa, with emphasis on Malawi's application of these laws in the 1992 trial of Chakufwa Chihana. This analysis is placed within the context of a review of the development of sedition laws in Britain and the United States and a critical review of the Malawi Supreme Court of Appeal decision in Chihana v. Republic. The article revisits the Court's opinion in Chihana to recommend that Parliament amend the relevant provisions of the sedition laws by providing a set of guidelines for courts to consider when determining what constitutes permissible restrictions of speech. It concludes that the establishment of a democratic order means, if anything, speech critical of government officials and its policies should remain uninhibited, unless restriction is essential to prevent an incitement to imminent disorderly conduct. Section I discusses the early European developments of sedition law and how courts interpreted and applied them. Sections II looks at the development of sedition laws in American jurisprudence and highlights the United States Supreme Court's struggle with the early cases. Section III reviews critically the Malawi Supreme Court of Appeal's opinion in Chihana in light of similar court opinions in the Commonwealth, Europe and the United States. This review will focus on two central issues in Chihana: the first is the inclusion of 'incitement to violence' as a necessary element for sedition; the second is the court's scrutiny of what constitutes permissive restrictions of speech in the context of the sedition analysis.